Occupational manganese exposure, reproductive hormones, and semen quality in male workers: A cross-sectional study. (January 2019) - Yang, Haibo; Wang, Jifeng; Yang, Xinxin; Wu, Fengdi; Qi, Zhipeng; Xu, Bin; Liu, Wei; Deng, Yu
It has been found that exposure to manganese (Mn) could induce reproductive dysfunction, but its occupational risk in male workers is unclear. This study aims to assess the association of occupational Mn exposure with reproductive hormones and semen quality in a cross-sectional study. Urinary Mn, semen quality, and reproductive hormones were explored in 84 male workers occupationally exposed to Mn and 92 referents. Multiple linear regression analyses were used to assess the relationship. Urinary Mn levels in Mn-exposed workers ranged from 0.56 to 34.25 µg/L, and the average level was 15.92 ± 8.49 µg/L. Compared with the control group, gonadotropin-releasing hormone (GnRH) levels and luteinizing hormone (LH) levels increased significantly and the levels of testosterone (TSTO) decreased significantly in the Mn-exposed group. There was a significant positive linear association between urinary Mn and GnRH and LH, while the linear association between urinary Mn and TSTO was negative. Sperm progressive motility and total motility decreased significantly in the Mn-exposed group. There was a significantly negative linear association between urinary Mn and sperm progressive motility and total motility. In conclusion, occupational Mn exposure was inversely associated with reproductive health of male workers, resulting in the abnormality of hormones secretion and decrease of sperm motility.